Citizen police academies: Community policing or community politics? - Jordan, W. T. (American journal of criminal justice, 2000)
Citizen police academies (CPAs) have become common in the United States. These programs have a great deal of potential to enhance community-policing efforts in two ways. First, they provide a setting where citizens can learn more about the operations of their local law enforcement agencies. Second, they allow participants to enter into an open and ongoing dialogue with agency representatives. This paper reports findings from a national survey of CPA coordinators. It questions the current status of CPAs as an element of community policing, as opposed to public or political relations.